A framework for managing change in lean manufacturing implementation - Nordin, Norani (2011)
Lean manufacturing is a proven approach for success in manufacturing industry.However, several organisations failed in their attempt to implement lean manufacturing system.The transition to lean manufacturing requires radical change which involves a total reshaping of purpose, system and culture of the organisation.The purpose of this paper is to develop a framework that could assist a manufacturing firm to implement lean manufacturing system successfully.The insights of literature and multiple case studies are combined to develop the organisational change framework.Leadership and direction, and change agent system found to be the most critical factors in managing change to lean manufacturing.Furthermore, the smooth transition also requires effective communication, workers’ empowerment and lean review system.Failure in recognising the required organisational change factors to be adapted in lean transition may hinder the long-term benefits of the company.